{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

m2k_dfq_scorcp

# m2k_dfq_scorcp - Second Order Differential Equations...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Second Order Differential Equations; Complex Roots of the Characteristic Equation Again considering the mass-spring system of the previous lec- ture, we note that if there is no damping in the system, so that γ = 0, then we have the differential equation m d 2 y dt 2 + k y = 0 . Here the characteristic equation is m r 2 + k = 0; the roots satisfy r 2 =- k m . This equation has no real solutions; the solutions are the complex numbers r 1 = v u u t k m i , r 2 =- v u u t k m i , where i has the property i 2 =- 1. What form can we expect the solutions to take in this case? Since the term k y is independent of t , we can proceed by the “change of variable method” introduced earlier for general autonomous second order equations; we set dy dt = z and then have, with K 2 = k m , z dz dy =- k m y ≡ - K 2 y, or z dz =- K 2 y dy. Integrating, we have z 2 2 =- K 2 y 2 2 + ˆ c. 1 Let us consider the case wherein c > 0 and rename ˆ c ≡ K 2 c 2 2 . Then we have z = K q c 2- y 2 and the equation dy dt = z becomes dy dt = K q c 2- y 2 , or 1 K √ c 2- y 2 dy = dt. Now let y = c w and we have 1 K 1 √ 1- w 2 dw = dt ⇒ 1 K sin- 1 w = t + ˆ d so that y = c w = c sin( Kt + K ˆ d ) and, renaming K ˆ d as d , y = c sin( Kt + d ) = c (sin Kt cos d + cos Kt sin d ) . Then letting c 1 = c cos d, c 2 = c sin d , we finally have y ( t, c 1 , c 2 ) = c 1 sin Kt + c 2 cos Kt ; K = v u u t k m ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 6

m2k_dfq_scorcp - Second Order Differential Equations...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online